2015
DOI: 10.1177/0300985815604725
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Amyloid A Amyloidosis in Island Foxes (Urocyon littoralis)

Abstract: Systemic amyloid A (AA) amyloidosis is highly prevalent (34%) in endangered island foxes (Urocyon littoralis) and poses a risk to species recovery. Although elevated serum amyloid A from prolonged or recurrent inflammation predisposes to AA amyloidosis, additional risk factors are poorly understood. Here we define the severity of glomerular and medullary renal amyloid and identify risk factors for AA amyloidosis in 321 island foxes necropsied from 1987 through 2010. In affected kidneys, amyloid more commonly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
(89 reference statements)
1
10
0
2
Order By: Relevance
“…The only other inflammatory lesion evaluated in our study was interstitial lymphoplasmacytic nephritis which showed stronger and more significant correlations with kidney and liver amyloidosis than gastritis. Similarly, nephritis was found to be an important risk factor for kidney amyloidosis in Island foxes [Gaffney et al, ]. In addition, other factors have been implicated in the pathogensis of amyloidosis in cheetahs.…”
Section: Discussionmentioning
confidence: 99%
“…The only other inflammatory lesion evaluated in our study was interstitial lymphoplasmacytic nephritis which showed stronger and more significant correlations with kidney and liver amyloidosis than gastritis. Similarly, nephritis was found to be an important risk factor for kidney amyloidosis in Island foxes [Gaffney et al, ]. In addition, other factors have been implicated in the pathogensis of amyloidosis in cheetahs.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic renal disease is a common age-related disease in many species including domestic cats[ 47 , 49 , 64 ], dogs[ 65 ], Island foxes[ 66 ], the great apes[ 67 ] and naked mole-rats[ 68 ]. As in humans[ 69 ], older cats have more CRD, interstitial fibrosis, sclerotic glomeruli and fewer nephrons than younger cats[ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although gastritis is reportedly the most common inflammatory lesion in cheetahs[ 5 , 6 , 9 , 17 , 31 ] no statistically significant association was found between alimentary tract and renal disease in this population of cheetahs. Lymphoplasmacytic nephritis but not gastritis has been shown to have a strong positive correlation with amyloidosis in cheetahs, Island foxes and Abyssinian cats [ 13 , 66 , 78 ]. Medullary fibrosis is closely associated with medullary amyloidosis in cheetahs[ 6 , 13 ] as well as in Abyssinian cats[ 78 ] and Shar Pei dogs[ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Variation in the size and topography of the islands cause differences in temperature, precipitation, and wind [12] and likely has contributed to the divergence of the gut microbiome. These geographically differing variables, as well as differences in anthropogenic impacts, across the islands influence the diet [13,14] and pathogen prevalence [15][16][17][18] across fox populations. Knowing that diet and the immune system affect the gut microbiome, this system is ideal to test if geography correlates with gut bacterial communities.…”
Section: Introductionmentioning
confidence: 99%